Evaluate the source of information (Journal of Parents and Teachers, 2014)
This article presents, in a clear and concise manner, a set of questions related to authorship, content, structure and other important aspects to evaluate if a web page is useful, adequate and optimal to search for information in it.
Keywords: Web page; network; Internet; adequate search.